Permasalahan Pengelolaan Persampahan di Kota Tarakan - Ridwan Mulyawan; Rizqi Puteri Mahyudin; Badaruddin Badaruddin; Ahmadi Ahmadi (Sanitasi: Jurnal Kesehatan Lingkungan, 2020)
Various programs are implemented in the context of waste management in Tarakan City. The programs that have been implemented are Tabungan Lingkungan (Taling), Gerakan Pungut Sampah (GPS) and Sampah Semesta (Semua Mesti Terlibat). The program does not provide optimal impact based on the amount of waste generation that continues to increase. Waste ge-neration in 2011 amounted to 98.7 tons/day and in 2018 it increased 79.05% to 176.73 tons/day with the level of solid waste service reaching 68%. This study aims to determine the main pro-blems in waste management in Tarakan City. This type of research is descriptive research. The respondents were five people from five different agencies. Data collection techniques in the form of interviews to find out waste management problems. The qualitative data from the interviews are then converted into quantitative data so that hierarchical analysis can be done. Analysis of the data using the Analytic Hierarchy Process (AHP) method with Software Expert Choice 11. The main problem is obtained from the multiplication of indicator scores with priority aspect values. The results of the analysis show the main problem of solid waste management is the lack of a solid waste management budget (0.133); lack of garbage transport equipment (0,130); habit of residents in littering (0.118); sanctions in regulations are not implemented (0.114); and sanctions have less deterrent effect (0.107). The main problem of waste management in Tara-kan City is related to lack of solid waste management budget.